Perceptions and Representations of the Malagasy Environment Across Cultures
XIII, 263 p. 20 illus.
Keywords: This book examines the history and impact of environmental change in Madagascar. Drawing on interdisciplinary, ethnographic methodologies, the book presents local and global perspectives on current environmental changes and their drivers, from mining to development and deforestation. The book emphasizes the embeddedness of Malagasy peoples’ social relationships with the natural environment, and contrasts this with the way the Malagasy environment is viewed by international conservation organizations. Through the presentation of concrete case studies, the contributors assess the current controversy over the history and nature of human impact on the environment in Madagascar, and offer innovatory insights into how these controversies, which plague current policy making, can be settled. Frank Muttenzer is Privatdozent and Senior Lecturer in Anthropology at the University of Lucerne Gwyn Campbell is Founding Director of the Indian Ocean World Centre at McGill University, Canada. Jacques Pollini, a trained agronomist and academic researcher, is currently a Development Worker at the GIZ (German Society for International Cooperation) in Kindu, DR-Congo.